Produk Gagal yang Jadi Viral: Studi tentang Reverse Branding dalam Komunikasi Pemasaran - Vellicia Vellicia; Iswadi Iswadi (Journal of Innovative and Creativity, 2025)
The phenomenon of failed products going viral on social media reflects a paradigm shift in digital marketing communication. Reverse branding—a marketing strategy that deliberately embraces product failures or criticisms as part of the brand narrative—has proven effective in rebuilding positive brand image and increasing consumer engagement. This study aims to examine the effectiveness of reverse branding in the context of viral failed products and explore the opportunities and risks it entails. Using a qualitative approach based on literature review, this study highlights the role of social media, storytelling, and consumer participation in reshaping product and brand perceptions. The findings reveal that reverse branding can be a powerful strategy when implemented with honesty, creativity, and a deep understanding of the audience. However, it also carries potential risks if not managed properly, as it may lead to manipulative perceptions that harm brand reputation. This research contributes academically to the study of contemporary branding and offers practical implications for business actors, particularly MSMEs, in leveraging virality to strengthen their brand presence in the digital era.